The Effectiveness of Neurofeedback on Working Memory and Processing Speed Among Girl Students With Learning Disabilities - Roghieh Nooripour; Fardin Farmani; Farinaz Emadi; Nikzad Ghanbari; Peyman Hassani-Abharian; Joshua J. Matacotta (Gonabad University of Medical Sciences, 2022)
Background: Learning disorders (LDs) are diagnosed in children impaired in the academic skills of reading, writing, and/or mathematics. Children with LDs usually exhibit a slower resting-state electroencephalogram (EEG), corresponding to a neurodevelopmental lag. The present study aimed to investigate the effectiveness of neurofeedback treatment on working memory and processing speed among girl students with learning disabilities.  Methods: The design used in the current study was a quasi-experimental design, including pretest, post-test, and follow-up with a control group. Using the convenience sampling method, 40 girl students with LDs were selected from among all students referred to the psychological clinics in Tehran City, Iran, in the 2020-2021 academic year. Therefore, samples were assigned to two control and experimental groups (n=17). Samples were assessed for structured clinical interviews for DSM-IV (SCID), n-back task, and Stroop and reverse-Stroop tests. The experimental group received 20 sessions of neurofeedback and standard psychological intervention treatment, while the control group received only standard interventions. Mixed repeated analysis of variance, independent t tests, and chi-square were used for data analysis. Results: The findings showed that neurofeedback treatment improved all the components of working memory (correct answer and correct response time) and processing speed in girl students with LDs during a two-month follow-up (P<0.0001). Conclusion: It is recommended that the principles and concepts of neurofeedback treatment, confirmed in the current study, be considered an educational mission and executive task for school counselors for girls with learning disabilities.